Significant Gene Biomarker Tyrosine Kinase Non-receptor 2 Mediated Cell Proliferation and Invasion in Colon Cancer - Ling, Sunkai; He, Yanru; Li, Xiaoxue; Ma, Yu; Li, Yuan; Kong, Bo; Huang, Peilin (Frontiers in Genetics, 2021)
Objective: The present research aimed to investigate the expression and biological function of TNK2 and miR-125a-3p in colon cancer. Materials & methods: The expression of TNK2 and miR-125a-3p in colon cancer tissue samples was analyzed by Public databases including UALCAN and Oncomine. Then we verified their expression in colon cancer cell lines by qRT-PCR and Western Blot. By regulating the expression of TNK2 and miR-125a-3p in colon cancer cells, their functions and potential mechanisms were explored. Results: The expression of TNK2 was overexpressed in colon cancer cell lines, and it was found to directly bind to miR-125a-3p, which was down-regulated in colon cancer cell lines. Their expressions can affect the proliferation and invasion of colon cancer. Additionally, Colon cancer patients with lower TNK2 expression had a better prognosis than those with higher TNK2 expression. Conclusion: Our results demonstrated that TNK2 and miR-125a-3p played a critical role in colon cancer, and they could also be served as biomarkers and potential prognostic markers for colon cancer.